2001
DOI: 10.1002/1615-9861(200102)1:2<248::aid-prot248>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic glycosylation

Abstract: With the advances of molecular biology and with improved analytical techniques a significant change of perception has taken place regarding prokaryotic glycoproteins. Glycosylation of proteins from prokaryotes is no longer considered a specific feature of certain organisms but has been demonstrated for many archaea and bacteria. Besides the occurrence of glycosylated enzymes, antigens and other cell envelope components, surface layer (S-layer) glycoproteins represent the best-studied examples of glycosylated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Owing to the reducing environment in the bacterial cytoplasm, it is often not feasible for proteins to form disulfide bonds. Eukaryotic post‐translational glycosylation, which is rather important for many functions of the displayed polypeptides,49 is not possible either 50…”
Section: Combinatorial Methods/directed Evolutionmentioning
confidence: 99%
“…Owing to the reducing environment in the bacterial cytoplasm, it is often not feasible for proteins to form disulfide bonds. Eukaryotic post‐translational glycosylation, which is rather important for many functions of the displayed polypeptides,49 is not possible either 50…”
Section: Combinatorial Methods/directed Evolutionmentioning
confidence: 99%
“…Although protein glycosylation was long believed to be restricted to Eukarya, it is now clear that bacteria can also form protein-attached N-glycans via asparagine residues, as well as O-glycans via threonine and/or serine residues (Messner, 2004;Szymanski & Wren, 2005;Weerapana & Imperiali, 2006;Abu-Qarn et al, 2008). Most studies on bacterial protein glycosylation revealed specific O-glycan attachment to one or two abundant polymeric surface proteins such as flagellins, pilins and S-layer proteins (Schaffer et al, 2001;Benz & Schmidt, 2002;Fletcher et al, 2007). Moreover, a limited number of general glycosylation systems have been described in bacteria, including the Nglycosylation machinery in Campylobacter jejuni and related species (Fig.…”
Section: Lactobacillus Glycoproteins?mentioning
confidence: 99%
“…Until recently most of the protein glycosylation has been found on eucaryotic proteins although now it is more evident that glycosylation in procaryotes combines a much greater diversity of glycan composition, linkage units, and glycosylation sequences on polypeptides (6).…”
Section: Forms Of Glycosylationmentioning
confidence: 99%